Perceptual Mapping Marketplace Tiktok Shop, Tokopedia, Shopee, Lazada, Blibli: Positioning Marketplace Based on Indonesia Online Shopper Preferences - Waoma, Samalua; ., Rahmat; ., Al-Amin; ., Zuwardi; Izmuddin, Iiz; Judijanto, Loso (Journal of Ecohumanism, 2024)
Technology is always developing, every technological development will affect human activity, every technology needs to be adapted to society, besides that the world of business competition is also very tied to technological developments, companies that are able to collaborate with technology will be able to provide the totality of their services with excellence, based on people’s preferences for The use of the marketplace examined in this perceptual mapping paper shows that the relationship between technology and humans is very high, and the business competition that is created is very clear. This paper uses multidimensional scaling analysis by collecting 153 respondents’ perceptions from questionnaires distributed in Indonesia. In the results of the MDS test, the competition between the marketplace Tiktok and Tokopedia is very close or the similarity of the attributes studied is very high. This paper is intended for several companies that want to innovate in order to remain competitive with the changes that are happening.Positioning